2003
DOI: 10.1051/0004-6361:20031248
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced collisional growth of a protoplanet that has an atmosphere

Abstract: Abstract. Once a protoplanet becomes larger than about lunar size, it accumulates a significant atmosphere that surrounds the solid core. When a planetesimal approaches the protoplanet, it interacts with the atmosphere. If enough energy of the planetesimal is lost by gas drag of the atmosphere, it is captured in the atmosphere even if its original trajectory would not lead to a direct collision with the solid core of the protoplanet. This increases the collision rate, resulting in faster growth of the protopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
171
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(177 citation statements)
references
References 22 publications
5
171
1
Order By: Relevance
“…Long before this size is reached, protoplanets bind the nebular gas and form atmospheres that will enhance the capture radius (Inaba & Ikoma 2003;Tanigawa & Ohtsuki 2010). According to the results of Inaba & Ikoma (2003) this will perhaps become important when oligarchs reach 0.1 M ⊕ 3 . Our expression for the impact radius and collision rates, therefore, are lower limits when protoplanets are surrounded by a thick atmosphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long before this size is reached, protoplanets bind the nebular gas and form atmospheres that will enhance the capture radius (Inaba & Ikoma 2003;Tanigawa & Ohtsuki 2010). According to the results of Inaba & Ikoma (2003) this will perhaps become important when oligarchs reach 0.1 M ⊕ 3 . Our expression for the impact radius and collision rates, therefore, are lower limits when protoplanets are surrounded by a thick atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Gas drag can provide some relief since, by damping the random motions of the planetesimals, the gravitational focusing is kept large. Moreover, the capture probability of planetesimals is also significantly increased when (proto)planets are surrounded by atmospheres (Inaba & Ikoma 2003;Tanigawa & Ohtsuki 2010) -again, gas drag is the mechanism that facilitates their accretion. Still, it is unclear if these effects are sufficient to overcome the timescale problem, i.e., to grow protoplanets to ∼10 M ⊕ within the time the gas disk dissipates (∼10 6 yr); see Levison et al (2010) for a recent review.…”
Section: Introductionmentioning
confidence: 99%
“…Inaba & Ikoma (2003) showed that the presence of a dense atmosphere increases the cross section of planetesimals and they derived expressions to quantify this effect. However, Ormel & Kobayashi (2012) showed that for small particles interacting in the settling regime the presence of an atmosphere does not yield an increase in the cross section.…”
Section: Presence Of An Atmospherementioning
confidence: 99%
“…First, protoplanets with masses over ∼0.1 M ⊕ (corresponding to radii of about 5000 km forρ p = 1 g cm −3 ) begin building a hydrogen-helium atmosphere which progressively enhances their cross section (Inaba & Ikoma 2003;Tanigawa & Ohtsuki 2010). When modeling this effect with the approach of Ormel & Kobayashi (2012), we find that the effect is significant at the high end of the radius range considered here, but without affecting our conclusions: the filtering efficiency remains low even for these Earth-mass protoplanets when in the settling regime, and extremely low in the hydrodynamical regime.…”
Section: Filtering By Protoplanetsmentioning
confidence: 99%
“…For the purpose of the collision rate, the capture radius of the protoplanet should depend upon the mass of the protoplanet, upon the planetesimals' velocity with respect to the protoplanet, upon the density profile of the envelope, ρ(r), and upon the size of the accreted planetesimals (smaller planetesimals are more affected by the gas drag of the envelope and therefore are easier to capture). As in Guilera et al (2010), here we adopt the prescription of Inaba & Ikoma (2003) where the capture radius R can be obtained by solving the following equation…”
Section: The Accretion Rate Of Solidsmentioning
confidence: 99%